Agrippina : sex, power, and politics in the early Empire - Barrett, Anthony, 1941- (Yale University Press, 1996)
Barrett argues that Agrippina - mother of Nero, wife of Claudius and brother to Caligula - has been misunderstood and had much influence and power in her own right.